Resiliensi Remaja “high-risk” Ditinjau dari Faktor Protektif - Rina Mulyati (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2009)
The main purposes of this study were to identify resiliency level within high-risk adolescence and to examine the influence of protective factors (social skills, problem solving skills, autonomy, internal locus of control, sense of purpose, participation in group activities, supportive environment and community aspiration) for resiliece level within respondents. Respondents were selected with purpossive sampling technique and 38 “high-risk” adolescence, 44.74% boys and 55.26% girls were then participating in this reseach and none of them were ever associated nor involved in criminal conduct. Data then collected using questionaires and also interview for selected respondents, as additional method. The results demonstrated the high level of resilience within respondents and identified 3 contributing factors toward adolescence resiliency level : Social skills ( = .880); Sense of purpose ( = .442); Community aspiration ( = .511).Keywords : resilience, high-risk adolescence